Bulky Phenyl Modifications of the Silanide Ligand Si(SiMe3)3 – Synthesis and Reactivity. Issue 22 (16th October 2017) - Schmidt, Patrick; Fietze, Sascha; Schrenk, Claudio; Schnepf, Andreas
Abstract : The synthesis and structural characterization of bulkier variations of the very common organometallic compound M Si(SiMe3 )3, namely M Si(SiMe3 )(SiPh3 )2 3 and M Si(SiPh3 )3 [ M = Li (1 ), K (5 )] are presented, which can be synthesized via a step by step exchange of SiMe3 groups by bulkier SiPh3 groups. This synthetic route is high selective and is performed in good yields via the silanes Si(SiMe3 )2 (SiPh3 )2 (2 ) and Si(SiMe3 )(SiPh3 )3 (4 ). Additionally, the corresponding silanes HSi(SiMe3 )(SiPh3 )2 (6H ) and HSi(SiPh3 )3 (7H ) are obtained via the reaction of3 and5 with aqueous HCl, respectively. Oxidation of6H with CCl4 gives the chlorsilane Cl‐Si(SiMe3 )(SiPh3 )2 (6Cl ). The bulkiest chlorsilane Cl–Si(SiPh3 )3 (7 ) is obtained by the reaction of5 with E Cl2 ( E = Sn, Pb). Abstract :